Spider Venom Peptide Pn3a Inhibition of Primary Afferent High Voltage-Activated Calcium Channels - McArthur, Jeffrey R.; Munasinghe, Nehan R.; Finol-Urdaneta, Rocio K.; Adams, David J.; Christie, Macdonald J. (Frontiers in Pharmacology, 2021)
Despite potently inhibiting the nociceptive voltage-gated sodium (Nav) channel, Nav1.7, μ-theraphotoxin Pn3a is antinociceptive only upon co-administration with sub-therapeutic opioid agonists, or by itself at doses >3,000-fold greater than its Nav1.7 IC50 by a yet undefined mechanism. Nav channels are structurally related to voltage-gated calcium (Cav) channels, Cav1 and Cav2. These channels mediate the high voltage-activated (HVA) calcium currents (ICa) that orchestrate synaptic transmission in nociceptive dorsal root ganglion (DRG) neurons and are fine-tuned by opioid receptor (OR) activity. Using whole-cell patch clamp recording, we found that Pn3a (10 µM) inhibits ~55% of rat DRG neuron HVA-ICa and 60-80% of Cav1.2, Cav1.3, Cav2.1 and Cav2.2 mediated currents in HEK293 cells, with no inhibition of Cav2.3. As a major DRG ICa component, Cav2.2 inhibition by Pn3a (IC50 = 3.71 ± 0.21 µM) arises from an 18 mV hyperpolarizing shift in the voltage dependence of inactivation. We observed that co-application of Pn3a and µ-OR agonist DAMGO results in enhanced HVA-ICa inhibition in DRG neurons whereas co-application of Pn3a with the OR antagonist naloxone does not, underscoring HVA channels as shared targets of Pn3a and opioids. We provide evidence that Pn3a inhibits native and recombinant HVA Cavs at previously reportedly antinociceptive concentrations in animal pain models. We show additive modulation of DRG HVA-ICa by sequential application of low Pn3a doses and sub-therapeutic opioids ligands We propose Pn3a’s antinociceptive effects result, at least in part, from direct inhibition of HVA-ICa at high Pn3a doses, or through additive inhibition by low Pn3a and mild OR activation.